2016
DOI: 10.5194/hess-20-2965-2016
|View full text |Cite
|
Sign up to set email alerts
|

Improving together: better science writing through peer learning

Abstract: Abstract. Science, in our case the climate and geosciences, is increasingly interdisciplinary. Scientists must therefore communicate across disciplinary boundaries. For this communication to be successful, scientists must write clearly and concisely, yet the historically poor standard of scientific writing does not seem to be improving. Scientific writing must improve, and the key to long-term improvement lies with the early-career scientist (ECS). Many interventions exist for an ECS to improve their writing, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…For example, students of three undergraduate plant science courses at the University of Wisconsin-River Falls found peer-review was useful to improving their oral and written assignments as well as their grades (Ortiz-Ribbing and Zlesak, 2015). Another study of early career scientists showed that peer learning can allow for improvement in writing and communications skills (Stiller-Reeve et al, 2016).…”
Section: Peer Review and Instructor Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, students of three undergraduate plant science courses at the University of Wisconsin-River Falls found peer-review was useful to improving their oral and written assignments as well as their grades (Ortiz-Ribbing and Zlesak, 2015). Another study of early career scientists showed that peer learning can allow for improvement in writing and communications skills (Stiller-Reeve et al, 2016).…”
Section: Peer Review and Instructor Feedbackmentioning
confidence: 99%
“…Incorporating peer and instructor review of written projects can be an additional strategy to further help students with writing improvement (Kaufman and Schunn, 2011;Stiller-Reeve et al, 2016). In a recent study, about 37% of students stated peer review improved their writing (Corcelles et al, 2017).…”
mentioning
confidence: 99%
“…CC BY 4.0 License. students and taking part in scientific discussions, as well as contributing to better written research proposals and journal publications (Stiller-Reeve et al, 2016, and references therein).…”
Section: -Passionmentioning
confidence: 99%
“…Following the formation of the Intergovernmental Panel on Climate Change (IPCC) and the US Senate testimony of James Hansen in 1988, climate science has increasingly become a topic of political debate, media coverage and part of the daily discourse in our societies (Bolin, 2007;Ungar, 2016). Simultaneously, the scientific understanding of climate change has been rapidly expanding, with the number of climate change papers published per year growing exponentially (McSweeney, 2015) and the confidence in humans as the main cause of global warming going from insufficient to "extremely likely" (as defined by the IPCC First to Fifth Assessment Reports; Houghton et al, 1990;Stocker et al, 2013).…”
Section: Introductionmentioning
confidence: 99%